2014
DOI: 10.1007/s12576-014-0324-9
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous regulation of ovarian function by noxious somatic afferent stimulation

Abstract: It is well known that ovarian function is regulated by hypothalamic–pituitary–ovarian hormones. However, although several histological studies have described the autonomic innervation of the ovary, the involvement of these autonomic nerves in ovarian function is unclear. Recently, it has been shown that both the superior ovarian nerve (SON) and the ovarian nerve plexus (ONP) induce vasoconstrictor activity by activation of alpha 1-adrenoceptors, whereas the SON, but not the ONP, inhibits ovarian estradiol secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In the present study, the results obtained from Vh-treated and GTD-denervated animals support this idea. Uchida and Kagitani [ 48 ] reported that the electrical stimulation of the SON results in lower testosterone concentrations via the activation of alpha-1 adrenergic receptors, and in lower oestradiol levels by the activation of alpha-2 adrenergic receptors. The discrepancy between Uchida and Kagitani’s findings and the present study results on testosterone and oestradiol secretion regulation in the Vh-treated and GTD denervated animals may result from the destruction of noradrenergic neurons by GTD treatment, evidenced by the TH (activity / expression) reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the results obtained from Vh-treated and GTD-denervated animals support this idea. Uchida and Kagitani [ 48 ] reported that the electrical stimulation of the SON results in lower testosterone concentrations via the activation of alpha-1 adrenergic receptors, and in lower oestradiol levels by the activation of alpha-2 adrenergic receptors. The discrepancy between Uchida and Kagitani’s findings and the present study results on testosterone and oestradiol secretion regulation in the Vh-treated and GTD denervated animals may result from the destruction of noradrenergic neurons by GTD treatment, evidenced by the TH (activity / expression) reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the innervation of the ovaries by vagal parasympathetic and sympathetic nerves has been described, the involvement of these autonomic nerves in ovarian function has not yet been clarified [ 16 ]. Moreover, β-adrenoceptors have been identified on several types of cancer cells, including ovarian cancer cell lines [ 17 ], yet little is known about their effects on uterine contractility in gynecological cancers.…”
Section: Introductionmentioning
confidence: 99%
“…An individual animal was lying with the left ovary exposed following a horizontal incision of about 2 cm and removal of abdominal fat. Based on the location of the SON nerve innervating the ovary (Uchida and Kagitani, 2014;Pastelin et al, 2017) and as shown in Figure 6A, the SON was cut with scissors. This was following by suturing the wound and kept warm to avoid infection.…”
Section: Unilateral Son Denervation (Sonx)mentioning
confidence: 99%